Autonomous homing control of a powered parafoil with insufficient altitude. (November 2016) - Tao, Jin; Sun, Qing-lin; Tan, Pan-long; Chen, Zeng-qiang; He, Ying-ping
Abstract: In order to realize safe and accurate homing of a powered parafoil under the condition of insufficient initial altitude, a multiphase homing path is designed according to the flight characteristics of the vehicle. With consideration that the traditional control methods cannot ensure the quality of path following because of the nonlinear, large inertial and longtime delay existed in the system and strong disturbances in a complex environment, a homing controller, composed of the vertical and horizontal trajectory tracking controllers, is designed based on active disturbance rejection control (ADRC). Then autonomous homing simulation experiment of the powered parafoil with insufficient altitude is carried on in a windy environment. The simulation results show that the planned multiphase homing trajectory can fulfill the requirements of fixed-point homing and flare landing; the designed homing controller can overcome the influences of uncertain items of the internal and external disturbances, track the desired homing path more rapidly and steadily, and possesses better control performances than traditional PID controllers. Highlights: Eight DOF dynamic model of powered parafoil is established. A multiphase homing trajectory under the condition of insufficient altitude is designed. Horizontal and longitude trajectory tracking controllers are designed based on ADRC. Fix-point homing and upwind landing with insufficient initial altitude are achieved through path following.